PROVINCIAL CENTER OF CEZAIR-I BAHR-I SEFID WHICH WAS SHAPED AFTER TANZIMAT (REFORMS) RODOS GOVERNMENT BUILDING - (:unkn) unknown (ISTANBUL UNIV, RESEARCH INST TURKOLOGY, DEPT ART HISTORY, 2018)
In the Ottoman architectural history literature, there is a limited number of researches on public building of 19th Century and their reflections on the socio-cultural sphere as well as of those which determine Ottoman daily life, interactions between various cultures and their intersections or conflicts in public sphere and daily life. Similarly, knowledge on sociocultural texture of the era as well as influence and change of government buildings of the era, which represent official ideology and power of the state, on social life and urban setting is also very limited. That's why data on the Rodos Government Building which is discussed on this paper for the first time, as well as information, sketches containing findings and space analyses and archive plan drawings which were published here, again, for the first time, are very important. Reform movements which were initiated by the centralist organization attempts during the reign of Sultan Mahmud II, and gained an impetus during Tanzimat, enabled formation of new administrative organs. Following proclamation of Vilayet Nizamname (Ordinance for Provinces) in 1864, some administrative modifications were undertaken and new elements were made prominent in formation of urban setting structures. Priority focal point amongst these structures was government building, representing the seat of the government, latter supplemented by court houses, telegram office, police station, jail, officer barracks, etc. The ideology and tendencies prevalent after Tanzimat reshaped locations of this newly emerging power. Rodos Government Building, which is center for Cezair-i Bahr-i Sefid Vilayet (Province) is one of the most important examples of this process. The relation amongst the ideology, politics and architecture, up to date, has been voiced in many senses and in many conceptual uses. The ideologies and trends which were dominant following Tanzimat and changes in the social life, shaped seat of power and were naturally reflected and found its expression on architecture as tokens of ideology and political power. This paper must be debated in this framework. Although authenticity of Rodos Government Building has today been spoiled, it is, with its prominent position on the island, an important symbol not only religious power but also political power of 390 years of Ottoman rule on the island.